Critical Residues for GTP Methylation and Formation of the Covalent m(7)GMP-Enzyme Intermediate in the Capping Enzyme Domain of Bamboo Mosaic Virus - Huang, Yih-Leh (American Society for Microbiology, 2004)
Open reading frame 1 of Bamboo mosaic virus (BaMV), a Potexvirus in the alphavirus-like superfamily, encodes a 155-kDa replicase responsible for the formation of the 5′ cap structure and replication of the viral RNA genome. The N-terminal domain of the viral replicase functions as an mRNA capping enzyme, which exhibits both GTP methyltransferase and S-adenosylmethionine (AdoMet)-dependent guanylyltransferase activities. We mutated each of the four conserved amino acids among the capping enzymes of members within alphavirus-like superfamily and a dozen of other residues to gain insight into the structure-function relationship of the viral enzyme. The mutant enzymes were purified and subsequently characterized. H68A, the mutant enzyme bearing a substitution at the conserved histidine residue, has an ∼10-fold increase in GTP methyltransferase activity but completely loses the ability to form the covalent m(7)GMP-enzyme intermediate. High-pressure liquid chromatography analysis confirmed the production of m(7)GTP by the GTP methyltransferase activity of H68A. Furthermore, the produced m(7)GTP sustained the formation of the m(7)GMP-enzyme intermediate for the wild-type enzyme in the presence of S-adenosylhomocysteine (AdoHcy), suggesting that the previously observed AdoMet-dependent guanylation of the enzyme using GTP results from reactions of GTP methylation and subsequently guanylation of the enzyme using m(7)GTP. Mutations occurred at the other three conserved residues (D122, R125, and Y213), and H66 resulted in abolition of activities for both GTP methylation and formation of the covalent m(7)GMP-enzyme intermediate. Mutations of amino acids such as K121, C234, D310, W312, R316, K344, W406, and K409 decreased both activities by various degrees, and the extents of mutational effects follow similar trends. The affinity to AdoMet of the various BaMV capping enzymes, except H68A, was found in good correlations with not only the magnitude of GTP methyltransferase activity but also the capability of forming the m(7)GMP-enzyme intermediate. Taken together with the AdoHcy dependence of guanylation of the enzyme using m(7)GTP, a basic working mechanism, with the contents of critical roles played by the binding of AdoMet/AdoHcy, of the BaMV capping enzyme is proposed and discussed.